Anemonin attenuates osteoarthritis progression through inhibiting the activation of IL‐1β/NF‐κB pathway. Issue 12 (23rd June 2017) - Wang, Zuqiang; Huang, Junlan; Zhou, Siru; Luo, Fengtao; Xu, Wei; Wang, Quan; Tan, Qiaoyan; chen, Liang; Wang, Jun; Chen, Hangang; Chen, Lin; Xie, Yangli; et al.
Abstract: The osteoarthritis (OA) progression is now considered to be related to inflammation. Anemonin (ANE) is a small natural molecule extracted from various kinds of Chinese traditional herbs and has been shown to inhibiting inflammation response. In this study, we examined whether ANE could attenuate the progression of OA via suppression of IL‐1β/NF‐κB pathway activation. Destabilization of the medial meniscus (DMM) was performed in 10‐week‐old male C57BL/6J mice. ANE was then intra‐articularly injected into joint capsule for 8 and 12 weeks. Human articular chondrocytes and cartilage explants challenged with interleukin‐1β (IL‐1β) were treated with ANE. We found that ANE delayed articular cartilage degeneration in vitro and in vivo . In particular, proteoglycan loss and chondrocyte hypertrophy were significantly decreased in ANE ‐treated mice compared with vehicle‐treated mice. ANE decreased the expressions of matrix metalloproteinase‐13 (MMP13), A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5), collagen X (Col X) while increasing Aggrecan level in murine with DMM surgery. ANE treatment also attenuated proteoglycan loss in human cartilage explants treated with IL‐1β ex vivo . ANE is a potent protective molecule for OA; it delays OA progression by suppressing ECM loss and chondrocyte hypertrophy partially by suppressing IL‐1β/NF‐κB pathway activation.